Teacher Professional Development in the Conditions of Education Transformation: New Regulatory Framework, Challenges and Opportunities - Byrka, Marian; Sushchenko, A.; Chubrei, O.; Yakubovska, N.; Dudchak, H. (Warszawa: University of Warsaw, 2022)
The article identifies new challenges and potential opportunities for teacher professional development in the context of nowadays Ukrainian education system transformation. The meaning of the research concepts of “transformation”, “modernization” and “reformation” were clarified. The “transformation” is interpreted as profound qualitative changes in the main structural components of the system, which are satisfactory to the challenges of modern society. The conducted literature review determined that the processes and changes in current education system of Ukraine should be defined not as modernization or reformation but as transformation. Nevertheless, the education transformation in Ukraine includes both modernization and reformation. A strong impact on teacher’s professional development maintains: 1) the system of general secondary education since it determines goals, terms, and rules of professional activities, and 2) the system of postgraduate pedagogical education that induces every teacher to find the most satisfactory methods, means and approaches to sustain high productivity and achieve complete self-realization in everyday routine. The current Ukrainian system of general secondary education is under changes performed according to the “Concept of the New Ukrainian School” implemented in the new “State Standard of Basic Secondary Education for 5-9 grades” and “Professional Standard “Teacher of general secondary education institution”. The existing Ukrainian system of postgraduate pedagogical education is revised in accordance with “Procedure for improving the qualifications of pedagogical and research and teaching staff” and conceptual and methodological principles of the implementation of the certification process outlined in the “Framework for continuous professional development of teachers”. The challenges that the new regulatory framework of Ukrainian education generates for teachers in the system of general secondary education and postgraduate pedagogical education are stressed, and new opportunities for teacher professional development are accentuated.
Keywords: transformation; regulatory framework; system of general secondary education; system of postgraduate pedagogical education; teacher professional development